2012
DOI: 10.1016/j.neuropharm.2012.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the Nociceptin/Orphanin FQ system in rat spinal cord following chronic morphine treatment

Abstract: Nociceptin/Orphanin FQ (N/OFQ) appears to contribute to the development of morphine tolerance, as blockade of its actions will block or reverse the process. To better understand the contribution of N/OFQ to the development of morphine tolerance, this study examined the effect of chronic morphine treatment on levels of N/OFQ and levels and activity of the N/OFQ peptide (NOP) receptor in spinal cord (SC) from male and female rats. Both male and female Wistar rats showed less responsiveness to morphine after subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Early studies also showed that intrathecal administration of N/OFQ causes the antinociceptive effect in the monkey and rodents [ 37 , 38 ]. Both of MOR and NOPR could be influenced on expression or affinity by chronic administration of exogenous opioids [ 41 , 42 ]. Several studies have been shown to cross influence another type of opioid receptors when continued activation of one type of opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies also showed that intrathecal administration of N/OFQ causes the antinociceptive effect in the monkey and rodents [ 37 , 38 ]. Both of MOR and NOPR could be influenced on expression or affinity by chronic administration of exogenous opioids [ 41 , 42 ]. Several studies have been shown to cross influence another type of opioid receptors when continued activation of one type of opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, chronic treatment with kappa- (κ-) opioid receptor agonist, U50,448H, decreased the expression of both κ- and δ- opioid receptors in the spinal cord and striatum of rats [ 43 ]. It has also been shown that chronic morphine influenced the N/OFQ systems [ 42 , 44 ]. Previous studies also provided evidence that NOPR and MOR not only formed a heterodimer with each other, but also regulated the desensitization function with each other [ 45 - 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…NOP receptor expression in the brains of MOR knockout mice did not differ from levels in wild-type mice (Slowe et al, 2001), suggesting that activation of MOR by endogenous agonists does not regulate the expression of NOP receptor supraspinally. In contrast, chronic activation of MOR with morphine increased NOP receptor expression in the dorsal spinal cord in mice and rats (Gouarderes et al, 1999;Ueda et al, 2000;Zhang et al, 2012b). Whether chronic morphine treatment also increases NOP receptor expression supraspinally is not yet known.…”
Section: Heterologous Regulation Of the Nop Receptormentioning
confidence: 99%
“…In addition, we identified upregulation of genes involved in nociception, including Pnoc , a gene coding for the precursor protein to nociception. Nociceptin levels in the spinal cord were higher in female rats treated with morphine (Zhang et al, 2012). Together, our findings support the notion that early postnatal exposure to morphine leads to changes in nociceptin signaling, although the potential role in hyperalgesia during opioid withdrawal in neonates is unknown.…”
Section: Discussionmentioning
confidence: 97%